Challenges Impacting Community Participation and Their Effect on Teaching and Learning: a Case Study of Rural Areas - Godfrey, Sango Mesheck (European Scientific Journal, ESJ, 2016)
This study sought to investigate challenges impacting community participation in schools and their effect on quality of education. The study was carried out in a qualitative paradigm in which a case study facilitated access to in-depth feelings, views, and opinions of community members and educators regarding their participation in providing education. Data were generated through focus group discussions with parents of children in the schools, community members without children in the schools, School Development Committee (SDC) members, and the teachers. In addition, data were generated through in-depth interviews with community leaders and school heads, observation as well as analysis of school documents such as minutes of SDC meetings, staff meetings, financial records, and children’s progress records. Data were transcribed and analysed manually through the cut and paste technique. The study found out that communities were involved in providing primary education through preparing children for school by providing food, school uniforms and stationery. Parents were also involved in children’s homework, as well as monitoring teacher and children’s attendance. In addition, parents were involved in preparing schools for children through providing labour and materials for constructing classrooms. Further, parents financed school budgets, and were involved in school governance. Challenges impacting community participation were centred on parents’ low standard of living, community attitude towards education, family income level, and school-community relations. Impact of community participation on teaching and learning included the following: hungry learners, narrow curriculum, unmotivated teachers, high rate of absenteeism and drop out, as well as ineffective school administration. The study recommended development and implementation of strategies for uplifting community standard of living through increasing family income levels and availability of food. The study, further recommends government policy on parent orientation on school processes and school based study sessions for parents and school children respectively. Government policies that prohibits the practice of sending away of children from school for non payment of levies should be reinforced.